Exogenous Model Merging by means of Model Management Operators - Boronat, Artur (Electronic Communications of the EASST, 2007)
In Model-Driven Engineering, model merging plays a relevant role in the maintenance and evolution of model-based software. Depending on the amount of metamodels involved in a model merging process, we can classify model merging techniques in two categories: endogenous merging, when all the models to be merged conform to the same metamodel; and exogenous merging, when the models to be merged conform to different metamodels. MOMENT (MOdel manageMENT) is a framework that is integrated in the Eclipse platform, and provides a collection of generic set-oriented operators to manipulate MOF models, following the Model Management discipline. In this paper, we study how model transformations are useful in a model merging process and we provide a solution for both kinds of model merging by means of model management operators and the QVT Relations language.